THE REMOVAL OF A FOREIGN BODY FROM THE LEFT TEMPORAL LOBE AND STRUCTURES OF THE MIDDLE CRANIAL FOSSA - V. A. Lukyanchikov; A. Y. Kordonsky; A. S. Tokarev (Неотложная медицинская помощь, 2018)
Penetrating brain injury is a rare but serious type of brain trauma. This article describes a successful surgical treatment of a victim with a wound of the left temporal lobe, great vessels and cranial nerves. Patients with damageв structures of the middle cranial fossa have to undergo surgical treatment in a specialized hospital with the possibility of comprehensive preoperative examination the availability of intensive care for neurosurgical patients with a full range of necessary medicines. Effective hemostatic materials are to be used to prevent intraoperative bleeding. In the absence of hemostatic materials, the operation is impractical.